Bibliometric study on depression and suicide in children and adolescents, 2003-2014 period. - Loo Martínez, Lucia (2020)
Depression and suicide in our children and adolescents is a public health problem that concerns society as a whole, the projections of the World Health Organiza tion on mental health in the child population are not encouraging for it Whereas it is important to know the state of scientific production in this area and become a reference for further research, OBJECTIVE: To analyze the scientific production pu blished in depression and suicide in children and ado lescents from 2003 to 2014 through the bibliometric analysis of 94 major items accessed databases, in Spa nish. Our findings are that the issues are investigated adolescent depression (23.4%) followed by depression in children (21.2%), and Colombia (26.6%), Mexico (17.02%) and Spain (15.9%) who have most published scientific production begins to increase from 2012. METHOD: This research is appliedsubstantive type (63.9%), where stands the descriptive correlational de sign (22.4%) and the simple descriptive (16.4%). Sam ples are usually nonprobabilistic intentional (65.7%) being  the  major  size  of  101  and  500  participants (40.3%) of them have been included men and women (95.5%), while teenagers investigated the secondary level ( 73%), 88% reported no socioeconomic status. Among the measuring instruments and questionnaires and psychometric scales (71%) tests are reported to be the children’s depression questionnaire used the CDS. Finally, over 84% of production is for multiple authorship.